Capable and considerate: Exploring the assigned attributes of an automated vehicle. (June 2021) - Johansson, Mikael; Ekman, Fredrick; Strömberg, Helena; Karlsson, MariAnne; Bligård, Lars-Ola
Abstract: Users' acceptance, and subsequent adoption, of automated vehicles is likely affected by the understanding they develop of the vehicle based on its driving style properties. This paper explores how driving style properties – as a type of tangible attribute – are perceived by users, and how they affect users' interpretations of AVs. 18 participants experienced a seemingly fully automated vehicle on a test track and were interviewed regarding the experience, both during and after. The findings show that the participants noticed most driving style properties but to different degrees, and that participants assigned four groups of intangible attributes: functionality attributes, ability, awareness, and character, where the last three represent higher-order attributes. These intangible attributes were directly affected by the driving style properties but was also formed by a chain of assigned intangible attributes. The findings also indicate two major themes of attributes which users perceive when experiencing an AV: the vehicle's capability and the consideration it shows towards its occupants and other road users. Because users assign attributes regarding capability and consideration, it is important to take into account that the vehicle is perceived in both these respects already in the early development stages, including in the vehicle's control algorithm development.